2020
DOI: 10.1155/2020/5380346
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Trials in Alzheimer’s Disease: A Hurdle in the Path of Remedy

Abstract: Human clinical trials seek to ameliorate the disease states and symptomatic progression of illnesses that, as of yet, are largely untreatable according to clinical standards. Ideally, clinical trials test “disease-modifying drugs,” i.e., therapeutic agents that specifically modify pathological features or molecular bases of the disease and would presumably have a large impact on disease progression. In the case of Alzheimer’s disease (AD), however, this approach appears to have stalled progress in the successf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 101 publications
0
65
0
1
Order By: Relevance
“…They further showed that modification of BMEVs with folate could enhance tumor-targeting ability as compared to the free drug [ 133 ]. Recently, because many clinical trials for the treatment of Alzheimer’s disease (AD) using synthetic drugs have failed [ 136 , 137 , 138 ], scientists are trying to develop targeted delivery using EVs and developing precision medicine-loaded EVs for the treatment of AD [ 139 , 140 ]. Plant-derived traditional medicine have been studied in preclinical models of AD [ 141 , 142 , 143 ].…”
Section: How Crucial Is the Origin Of Exosomes For Drug Delivery?mentioning
confidence: 99%
“…They further showed that modification of BMEVs with folate could enhance tumor-targeting ability as compared to the free drug [ 133 ]. Recently, because many clinical trials for the treatment of Alzheimer’s disease (AD) using synthetic drugs have failed [ 136 , 137 , 138 ], scientists are trying to develop targeted delivery using EVs and developing precision medicine-loaded EVs for the treatment of AD [ 139 , 140 ]. Plant-derived traditional medicine have been studied in preclinical models of AD [ 141 , 142 , 143 ].…”
Section: How Crucial Is the Origin Of Exosomes For Drug Delivery?mentioning
confidence: 99%
“…The lack of clear proof of efficacy of Aβ targeting therapies so far has raised skepticism regarding the validity of the amyloid hypothesis, driving researchers to explore tau pathology as a plausible therapeutic target, particularly as cognitive decline in AD exhibits a better correlation with tau accumulation than with Aβ deposition [ 218 , 219 , 220 , 221 ]. Monoclonal antibodies targeting abnormal forms of tau protein and particularly soluble oligomers which appear to be the most neurotoxic form of p -tau [ 222 ] are being explored for efficacy in AD.…”
Section: Indications In Neurologymentioning
confidence: 99%
“…Mutations in the genes APP, PSEN1 , and PSEN2 encoding for amyloid precursor protein, presenilin 1 and presenilin 2, respectively, account for most of the early-onset AD, while mutated apolipoprotein E ( APOE ) gene is frequently associated with late-onset AD (Silva et al, 2019 ). Such genetic defects were initially linked to amyloidosis—a well-known histopathological hallmark of AD, the removal of which has been attempted as a treatment; unfortunately, such clinical trials have failed (Oxford et al, 2020 ). While this appears to preclude amyloidosis as a primary causal factor for AD, it does not diminish the importance of genetic factors in AD, and continued efforts to give biological meaning to genetic information may facilitate the identification of aetiological agent(s) and/or key immunopathological factor(s), which ultimately are necessary for therapeutic discovery.…”
Section: Existing Evidence Suggests An Infectious Aetiology Of Neurodmentioning
confidence: 99%